Viscosities and excess energy of activation for viscous flow for binary mixtures of tetrahydrofuran with 1-butanol, 2-butanol and 1-chlorobutane at 283.15, 298.15 and 313.15 K - Mariano,A. (2000)
Kinematic viscosities of binary mixtures composed of tetrahydrofuran with 1-butanol, 2-butanol and 1-chlorobutane have been measured at 283.15, 298.15 and 313.15 K and atmospheric pressure for the whole range of compositions. The dynamic viscosity, the excess viscosity and the excess energy of activation for viscous flow were also calculated. The excess viscosity shows negative deviations from ideal behavior for the mixtures tetrahydrofuran with 1-butanol and 2-butanol and a small positive deviation for the binary tetrahydrofuran + 1-chlorobutane system. The experimental results have also been used to test some empirical and semiempirical equations adopted previously to correlate viscosity - composition data.